Pengembangan Digital Marketing Dalam Meningkatkan Kinerja Bisnis Bagi Pelaku Usaha Batik Baduta Kelurahan Tanggung Kecamatan Kepanjen Kidul Kota Blitar - Nafa Amalina; Arief Bachtiar; Kiky Asmara (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Baduta batik Blitar is an MSME that sells batik handicraft products. Barik itself is a work of a nation that is well known abroad. The batik craft center itself is a cultural tour that is visited by many domestic and foreign tourists. Almost every region in Indonesia has batik craft centers, especially in Java and its surroundings. UMKM Batik Baduta Blitar has been built since 2009, but UMKM Baduta has obstacles in carrying out digital marketing, which causes Batik Baduta Blitar customers to complain about the lack of information from Batik Baduta Blitar writing on Batik Baduta Blitar's social media. The application of digital marketing is carried out with the stages of literacy, training and development then application of programs that are in accordance with the conditions of the Baduta batik group. The results of this study are that with this problem the solution that can be applied is to create an online marketing strategy that includes digital marketing strategies, social media content, and copy writing. The existence of this online marketing strategy can make Batik Baduta Blitar MSMEs able to carry out marketing effectively and efficiently.